1962
DOI: 10.1002/jlac.19626540103
|View full text |Cite
|
Sign up to set email alerts
|

Über die Einwirkung von Wasserstoff auf einige metallorganische Verbindungen und Komplexe

Abstract: Bd. 654 6) Nachweis von Wosserstoff bei der alkalischen Zersetzung der Hydroxylambi-0-suvo nsaure: 56 g in 100 ccm Wasser geloste Hydroxylamin-0-sdfonsaure wurden zu einer Losung von 40g NaOH in 80ccm Wasser gefiigt. Das entweichende Gas fing man uber KOH-Losung in einer Btirette auf. Gaschromatographisch konnten Stickstoff, Ammoniak und Wasserstoff sowie Distickstoflmnoxyd nachgewiesen werden. Bei einem entsprechend durchgefiihrten Versuch rnit Methanol als Losungsmittel und Natriummethylat als Base entstande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(48 citation statements)
references
References 21 publications
1
45
0
2
Order By: Relevance
“…The entry of the dimethyltitanocene into the catalytic cycle to give an initial complex analogous to that proposed by Curtis et al could occur by the reactions shown in [3]- [5]. [3] CpzTiMez + HMezSiOSiMezH + This proposition is supported by the detection of both methane and EE' in the initial reaction products.…”
Section: Reactions Of Alkoxysilanes With Dimethyltitanocenesupporting
confidence: 61%
See 1 more Smart Citation
“…The entry of the dimethyltitanocene into the catalytic cycle to give an initial complex analogous to that proposed by Curtis et al could occur by the reactions shown in [3]- [5]. [3] CpzTiMez + HMezSiOSiMezH + This proposition is supported by the detection of both methane and EE' in the initial reaction products.…”
Section: Reactions Of Alkoxysilanes With Dimethyltitanocenesupporting
confidence: 61%
“…Dimethyltitanocene was synthesized by a literature procedure (5). The following compounds were obtained from Petrarch Systems Inc.: E'E', E'E, E'DE', E1D2E', E1D3E', D4, D4', D5, (MeO)3SiH, and Me(EtO)2SiH.…”
Section: Methodsmentioning
confidence: 99%
“…Silanes were prepared by LiA1H4 reduction of the appropriate chlorosilane using modifications of literature methods (17). Dimethyltitanocene was prepared by a literature procedure (9) and freshly recrystallized before use.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…The critical feature of the DMT reactions, and one which distinguishes DMT from its zirconium and hafnium analogues, is the explosive nature of the reaction that leads to reduced titanium species. In its strongly autocatalytic nature and its spatially inhomogeneous propagation, this reaction is very similar to the reaction of Hz with DMT (6,10). It is likely in both cases that titanocene is the chain carrier that is responsible for the branched chain character of these reactions.…”
Section: The Reactions Of Dipherzylsilarze and Metlzylplzenylsilanementioning
confidence: 82%